Povidone-Iodine Has a Profound Effect on In Vitro Osteoblast Proliferation and Metabolic Function and Inhibits Their Ability to Mineralize and Form Bone. Issue 9 (May 2016) - Newton Ede, Matthew P.; Philp, Ashleigh M.; Philp, Andrew; Richardson, Stephen M.; Mohammad, Saeed; Jones, Simon W.
Abstract : Study Design: A study examining the clinical protocol of scoliosis wound irrigation, demonstrating povidone-iodine's (PVI) effect on human osteoblast cells. Primary and immortal cell line osteoblasts were treated with 0.35% PVI for 3 minutes, and analyzed for proliferation rate, oxidative capacity, and mineralization. Objective: To model spinal wound irrigation with dilute PVI in vitro, in order to investigate the effect of PVI on osteoblast proliferation, metabolism, and bone mineralization. Summary of Background Data: Previously PVI irrigation has been proposed as a safe and effective practice to avoid bacterial growth after spinal surgery. However, recent evidence in multiple cell types suggests that PVI has a deleterious effect on cellular viability and cellular function. Methods: Primary and immortal human osteoblast cells were exposed to either phosphate buffered saline control or with 0.35% PVI for 3 minutes. Cellular proliferation was measured over the duration of 7 days by MTS assay. Oxygen consumption rate, extracellular acidification rate, and proton production rate were analyzed using a Seahorse XF e 24 Bioanalyzer. Protein expression of the electron transport chain subunits CII-SDHB, CIII-UQRCR2, and CV-ATP5A was measured via Western blotting. Mineralized bone nodules were stained with alizarin red. Results: Expressed as a percentage of normal osteoblast proliferation, osteoblasts exposed to 0.35% PVI exhibited a significant 24% decrease in proliferation after 24 hours. This was a sustained response, resulting in a 72% decline in cellular proliferation at 1 week. There was a significant reduction in oxygen consumption rate, extracellular acidification rate, and proton production rate ( P < 0.05), in osteoblasts that had been exposed to 0.35% PVI for 3 minutes, coupled with a marked reduction in the protein expression of CII-SDHB. Osteoblasts exposed to 0.35% PVI exhibited reduced bone nodule mineralization compared to control phosphate buffered saline exposed osteoblasts ( P < 0.01). Conclusion: PVI has a rapid and detrimental effect on human osteoblast cellular proliferation, metabolic function, and bone nodule mineralization. Level of Evidence: NA